The treatment gap for mental disorders in adults enrolled in HIV treatment programmes in South Africa: a cohort study using linked electronic health records. (17th May 2021) - Ruffieux, Y.; Efthimiou, O.; Van den Heuvel, L. L.; Joska, J. A.; Cornell, M.; Seedat, S.; Mouton, J. P.; Prozesky, H.; Lund, C.; Maxwell, N.; Tlali, M.; Orrell, C.; et al.
Abstract: Aims: Mental disorders are common in people living with HIV (PLWH) but often remain untreated. This study aimed to explore the treatment gap for mental disorders in adults followed-up in antiretroviral therapy (ART) programmes in South Africa and disparities between ART programmes regarding the provision of mental health services. Methods: We conducted a cohort study using ART programme data and linked pharmacy and hospitalisation data to examine the 12-month prevalence of treatment for mental disorders and factors associated with the rate of treatment for mental disorders among adults, aged 15–49 years, followed-up from 1 January 2012 to 31 December 2017 at one private care, one public tertiary care and two pubic primary care ART programmes in South Africa. We calculated the treatment gap for mental disorders as the discrepancy between the 12-month prevalence of mental disorders in PLWH (aged 15–49 years) in South Africa (estimated based on data from the Global Burden of Disease study) and the 12-month prevalence of treatment for mental disorders in ART programmes. We calculated adjusted rate ratios (aRRs) for factors associated with the treatment rate of mental disorders using Poisson regression. Results: In total, 182 285 ART patients were followed-up over 405 153 person-years. In 2017, the estimated treatment gap for mental disorders was 40.5% (95% confidence interval [CI] 19.5–52.9) for patients followed-up in private care, 96.5% (95% CI 95.0–97.5) for patients followed-up in public primary care and 65.0% (95% CI 36.5–85.1) for patients followed-up in public tertiary care ART programmes. Rates of treatment with antidepressants, anxiolytics and antipsychotics were 17 (aRR 0.06, 95% CI 0.06–0.07), 50 (aRR 0.02, 95% CI 0.01–0.03) and 2.6 (aRR 0.39, 95% CI 0.35–0.43) times lower in public primary care programmes than in the private sector programmes. Conclusions: There is a large treatment gap for mental disorders in PLWH in South Africa and substantial disparities in access to mental health services between patients receiving ART in the public v s the private sector. In the public sector and especially in public primary care, PLWH with common mental disorders remain mostly untreated.